Fungi Associated with Dieback and Pruning Wounds of Grapevines in South Africa - Ferreira, J.H.S.; Matthee, F.N.; Thomas, A.C. (South African Journal of Enology and Viticulture, 2017)
Isolations were made from discoloured tissue of grapevines showing dieback symptoms in the winter rainfall region. Fifteen fungal species were isolated, of which Sphaeropsis sp. Fusarium oxysporum, Eutypa lata (anamorph: Libertella blepharis A.L. Smith), Pestalotia quepini and Botrytis cinerea could be designated as parasites. E. lata was the most probable cause of the dieback phenomenon. Additional isolates representing ten fungal genera were isolated from discoloured wood in spurs from visually healthy grapevines while organisms representing 14 genera were isolated from lesions in grapevines exhibiting dieback symptoms. Aspergillus sp. was more common in the healthy and marginal zones while Sphaeropsis sp. occurred more often in the healthy zone and Phylosticta sp. in the discoloured zone of pruning stubs. In lesions from vines with dieback symptoms, Altemaria alternata was isolated more regularly from the marginal zone between healthy and discoloured wood, while E. lata and Trichoderma harzianum were isolated more often from the older part of the lesion. A succession of fungi in the colonisation of pruning wounds and in dieback lesions is suggested.